Enhancing Science Learning in Primary Schools: Development of Interactive Edu-Game Multimedia to Boost Student Motivation and Achievement - Sella Oktania; Windatul Hasanah; Lukmanul Hakim; Atin Fatimah (AL-ISHLAH: Jurnal Pendidikan, 2025)
The use of traditional learning media in elementary science education often fails to foster active participation or stimulate student motivation, leading to suboptimal learning outcomes. To address this, the development of interactive, game-based multimedia is proposed as a more engaging alternative. This study employed a Research and Development (RD) approach using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The participants were second-grade students from an elementary school in Serang City. Data were collected through validity and practicality instruments, motivation questionnaires, learning outcomes tests, and observation sheets. The developed educational game-based interactive multimedia was validated by experts and deemed suitable for classroom use. Student feedback indicated high practicality, with 93% of learners responding positively. The multimedia tool significantly improved student motivation by 33.3% and science learning outcomes by 88%. The findings demonstrate that incorporating educational games into multimedia learning tools can effectively enhance both engagement and academic performance in elementary science education. The digital format aligns with current technological trends and meets learners' needs more effectively than traditional media. Educational game-based interactive multimedia is a valid, practical, and effective solution for improving student motivation and learning outcomes in elementary science education.